2022
DOI: 10.1186/s12886-022-02350-w
|View full text |Cite
|
Sign up to set email alerts
|

Based on multiple machine learning to identify the ENO2 as diagnosis biomarkers of glaucoma

Abstract: Purpose Glaucoma is a generic term of a highly different disease group of optic neuropathies, which the leading cause of irreversible vision in the world. There are few biomarkers available for clinical prediction and diagnosis, and the diagnosis of patients is mostly delayed. Methods Differential gene expression of transcriptome sequencing data (GSE9944 and GSE2378) for normal samples and glaucoma samples from the GEO database were analyzed. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Differential gene expression analysis is a commonly used computational approach for identifying marker genes corresponding to a specified phenotype. A typical differential gene expression analysis often identifies a hundred or more differentially expressed genes (DEGs), where a considerable number of them might be highly correlated with one or more other DEGs ( Dai et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differential gene expression analysis is a commonly used computational approach for identifying marker genes corresponding to a specified phenotype. A typical differential gene expression analysis often identifies a hundred or more differentially expressed genes (DEGs), where a considerable number of them might be highly correlated with one or more other DEGs ( Dai et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of artificial intelligence, machine learning has provided more accurate glaucoma diagnosis based on imaging, visual field testing, clinical and transcriptomic data using supervised learning; results also have provided biological insight by revealing expression patterns from data using unsupervised learning ( Zheng et al, 2019 ; Alipanahi et al, 2021 ). Dai et al (2022) used Logistic Regression (LR), Random Forest (RF), and lasso regression (LASSO) for glaucoma diagnosis based on the DEGs and found diagnosis marker ENO2 by evaluating the efficiency of the classification model and the included features/genes. However, in this study, the classification model was based on a dataset with a very small number of samples (32 samples in total), thus the generalizability of the result is questionable, and needs further validation.…”
Section: Introductionmentioning
confidence: 99%
“…The gene set selected by SVM showed a superior performance in cancer classification compared to that selected by other selection methods. Dai et al found glaucoma diagnostic markers based on a logistic regression-RF (LR-RF) model coupled with experimental validation [13]. However, no study has been carried out using ML for PAH diagnosis and potential biomarker discovery and further validated the results using a pathway analysis and experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding the pathological changes in the TM microstructure induced by DEX treatment is essential for the development of effective therapies [7] . To date, many studies have employed a variety of experimental methods [such as RNA sequencing (RNA-seq)] to select differentially expressed genes (DEG) profiles of TM after exposure to steroid hormones at the whole genome level, resulting in complex and comprehensive datasets [8] . Systematically and comprehensively analysing the relationship between DEGs and differentially activated signalling pathways in DEX-treated and nontreated samples will help us gain new insights into the progression and treatment of SIG.…”
Section: Introductionmentioning
confidence: 99%